Behavioral Nudging and Financial Reporting Integrity: A Systematic Literature Review in Accounting and Management - Rommy Wijaya; Eko Supriyanto Hadi; Ririn Widyastuti Wulaningsih; Alief Ramdan; Winda Wulandari (Universitas Muhammadiyah Prof. DR HAMKA., 2026)
This study synthesizes and critically evaluates the development of research on behavioral nudging and financial reporting integrity through a Systematic Literature Review (SLR) of 33 Scopus-indexed peer-reviewed articles published between 2021 and 2026. Guided by the PRISMA 2020 protocol (Page et al., 2021), the selected studies were analyzed using the Theory-Context-Method (TCM) framework to identify theoretical developments, contextual patterns, methodological tendencies, and emerging research opportunities. The findings reveal that research in this field has evolved from a predominantly technical and compliance-oriented perspective toward a broader interdisciplinary understanding that integrates behavioral science, corporate governance, and digital transformation. The synthesis further demonstrates that financial reporting integrity should be understood as a multidimensional organizational construct jointly shaped by behavioral interventions, governance structures, and digital capabilities rather than by technical compliance alone. This review contributes in three important ways. Theoretically, it develops an integrated conceptual perspective that reconciles fragmented streams of accounting, governance, and behavioral research. Methodologically, it demonstrates the value of combining the PRISMA 2020 protocol with the TCM framework to produce a transparent and interpretive synthesis of interdisciplinary literature. Practically, the findings provide actionable insights for managers, auditors, and policymakers by highlighting the importance of integrating behavioral design principles with governance mechanisms and digital reporting systems to strengthen transparency, accountability, and financial reporting integrity. Finally, the review identifies future research directions emphasizing theoretical integration, contextual diversification, and methodological advancement